2015
DOI: 10.1111/bju.13378
|View full text |Cite
|
Sign up to set email alerts
|

Adherent perinephric fat at minimally invasive partial nephrectomy is associated with adverse peri‐operative outcomes and malignant renal histology

Abstract: A total of 245 patients undergoing MIPN were included in the study. The presence of APF was determined through keywords in operating notes, and radiographic data were obtained from preoperative cross-sectional imaging. Posterior fat thickness was measured between the renal capsule and the posterior abdominal wall at the level of the renal vein. Perinephric stranding was graded on a 0-3 severity scale. ResultsThe study included 123 men and 122 women, with a median age of 55 years, body mass index of 31.7, tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
87
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 24 publications
4
87
5
1
Order By: Relevance
“…The incidence of APF in our study was 17%, which was lower than the incidence rates in previous studies of Western cohorts (30-55%) [3,4,6,13]. BMI was associated with APF in this Asian cohort as it was in the Western cohorts, although the mean BMI (24 kg/m 2 ) in our study was smaller than those in Western studies (29-33 kg/m 2 ) [5,6,12]. Since Asians tend to have higher percentages of body fat than Caucasians do at equivalent BMIs [7,8], it could be supposed that the incidence of APF in Asians is close to that in Caucasians, in spite of the difference in their mean BMIs.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…The incidence of APF in our study was 17%, which was lower than the incidence rates in previous studies of Western cohorts (30-55%) [3,4,6,13]. BMI was associated with APF in this Asian cohort as it was in the Western cohorts, although the mean BMI (24 kg/m 2 ) in our study was smaller than those in Western studies (29-33 kg/m 2 ) [5,6,12]. Since Asians tend to have higher percentages of body fat than Caucasians do at equivalent BMIs [7,8], it could be supposed that the incidence of APF in Asians is close to that in Caucasians, in spite of the difference in their mean BMIs.…”
Section: Discussioncontrasting
confidence: 85%
“…The current results showed, however, that Asians had a lower incidence of APF at lower BMI levels compared to Caucasians. The predictors of APF other than MAP score reported in the Western cohorts were male gender, older age, obesity, waist circumference, and hypertension [3][4][5]. The current study indicated that male gender was a strong predictor of APF in multivariate analysis, although other metabolic factors, including older age, higher BMI, smoking habit, and history of hypertension were not associated with the presence of APF.…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…PSF is defined as thick and adherent perirenal fat (PF) that is difficult to dissect off the renal capsule and is well known to experienced urologists who are involved with partial nephrectomy (PN). It has been related to longer operating time, increased perioperative complications and conversion to open surgery . Currently there is no validated imaging marker to predict the presence of PSF and there is only a limited number of studies in the literature evaluating the prediction of PSF by preoperative imaging which all relied on CT or MRI for PF characteristics.…”
Section: Introductionmentioning
confidence: 99%